Comparison of experimental photonic and refractive index characteristics of the TBADN films with their theoretical counterparts - Örek, Cahit; Arslan, Faruk; Gündüz, Bayram; Kaygili, Omer; Bulut, Niyazi (Elsevier BV, 2018)
Abstract Photonic properties and refractive indexes of the TBADN films were investigated with various experimental and theoretical methods. The effects of the film thicknesses on the photonic properties of the TBADN films were examined. It was found that while the optical band gap of the TBADN film decreases with increasing film thickness, the refractive indexes exhibit a normal dispersion behavior for both experimental and theoretical techniques. This study shows that the most suitable optoelectronic parameters for optoelectronic devices can be achieved with film thicknesses. The TBADN molecule was found to have a lower refractive index in the chloroform solvent.
Keywords: Photonic properties; TBADN films; Anthracene; Film thickness; Refractive index